Comunidades y agentes del estado en la construcción de formas cotidianas de negociación. Costa Rica, 1850-1914 - Alvarenga Venutolo, Patricia (Revista de historia., 2004)
This article constitutes an analysis of the construction of power, in a predominantly rural world of the Central Valley of Costa Rica, based on the interaction between government agents and rural communities. It intends to unveil a dimension of hegemonic practices in the organization of collective work for the development of infrastructure required for the process of commercialization of the economy. The steering power of the government agents is acknowledged, debated on, and negotiated by the peasant communities, intersected by economic and regional differences and conflicts. Points of coincidence and fracture between communities are woven into the discursive constructions facing public policies, whether in a subtle or open manner.